Implementasi Nilai-Nilai Kebangsaan Yang Bersumber Pancasila Dan UUD 1945 Pada Manajemen Security Tentang Perlindungan Data Pribadi Di Era Digital - Naely Fauziyah Mukti; Edy Soesanto; Luthfi Nur Ardyansyah (International Forum of Researchers and Lecturers, 2024)
The digital era brings major changes in various aspects of life, including in the field of national security. National security threats in the digital era no longer only come from military forces, but also from various forms of cyberattacks. Cyber threats become complex and diverse, and national resilience is tested by the emergence of various structured and organized cyber attacks. Pancasila is the basis of the Constitution of the Republic of Indonesia, which serves as the legal basis of the Indonesian state which mandates the implementation of national security to protect society. Security management is key in facing national security challenges in the digital era. This paper discusses the implementation of security management that can improve national security and cyber threats. This research aims to analyze the implementation of security management in national resilience in the digital era. This research uses a qualitative descriptive method with a case study approach.